2009
DOI: 10.1163/187103209x440209
|View full text |Cite
|
Sign up to set email alerts
|

Islamists in Jordan: Promoters of or Obstacles to Female Empowerment and Gender Equality?

Abstract: This study deals with the Muslim Brotherhood's reception of CEDAW (Convention on the Elimination of All Forms of Discriminations against Women) in Jordan. In view of the Arab Human Development Report (AHDR) and interviews with several political actors in Jordanian society it is possible to evaluate Islamist ideas on women's rights. The main aim is to investigate whether Jordanian Islamists are promoters of or obstacles to female empowerment and gender equality. By analyzing various political stands it became a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…It is suggested that in recent years there has been a significant improvement in female engagement in the labour force within the Middle East [104] with increased levels of economic participation [105] greater social voice [106], and increased legal recognition [40]. Cumulatively, these factors can be regarded as "empowerment" insofar as females have obtained increased levels of recognition, power and status in their daily lives.…”
Section: Empowerment In the Middle Eastmentioning
confidence: 99%
See 1 more Smart Citation
“…It is suggested that in recent years there has been a significant improvement in female engagement in the labour force within the Middle East [104] with increased levels of economic participation [105] greater social voice [106], and increased legal recognition [40]. Cumulatively, these factors can be regarded as "empowerment" insofar as females have obtained increased levels of recognition, power and status in their daily lives.…”
Section: Empowerment In the Middle Eastmentioning
confidence: 99%
“…It is also noted that over the last decade several Middle Eastern nations have pursued an economic policy of increasing national levels of literacy and education in order to boost economic output and to capitalise upon internal intellectual capital [110]. The unintended outcome of this is a highly educated younger generation many of whom have studied in the West and who have brought back with them cultural ideals associated with democracy [106].…”
Section: Empowerment In the Middle Eastmentioning
confidence: 99%
“…8 The Islamist concept of 'justice' builds on a biological understanding of 'equity', where men and women should fulfil social roles according to the divinely created biological conditions of each gender. 9 In this context claims of gender equality or gender equal opportunities are regarded as means for oppression of women, as women would be forced to go beyond their 'nature' if they get tasks which are not suitable for their biological constitution (Roald 2009 What is not taken into consideration in this argumentation is that the outcome of the biological reductionism inherent in the notion of 'the beneficial patriarchy' is an inequality of men's and women's legal rights in the Islamic family legislation, which gives 'bad'…”
Section: The Benevolent Patriarchymentioning
confidence: 99%
“…13 It is important to see this ideal image of 'the benevolent patriarchy' as a product of on the one hand, the upper middle class educated elite (Islamists often belong to this elite), who rarely have to deal with the social and economic problems of the big majority of the lower middle class, and on the other, a patriarchal collectivistic structure with focus on male interests. At the same time it is important to be aware of that the ideal image of 'the benevolent patriarchy' is internalised by most classes and by men and women alike in Palestinian communities (Roald 2009 (Roald 1994;2008;2009). The present study will draw on material from these fieldworks in Jordan.…”
Section: The Benevolent Patriarchymentioning
confidence: 99%
See 1 more Smart Citation